âGREEN MAPâ SISTEM MONITORING DAN PETA VISUALISASI DISTRIBUSI KUALITAS UDARA BERBASIS WEB - Widianjaya, Adhe; Handoko, Rafika Nilasari (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Degradation of air quality condition attracts worldwide attention. Less and poor informations cause the low people attention for this threatening environment condition. Monitoring facilities managed by government today, arenât effective yet in the quality and quantity point of view. Their price were also so expensive causing low quality and numbers of monitoring devices. Team has developed web based air quality map and its sensor devices as the solution for this issues. Team has done data mining in the responsible government agencies and people of Surabaya to support the result later. Team then did the development of sensor devices and its web server. Three sensor devices which were placed in several points in Surabaya for testing and evaluation. The âGreen Mapâ system gave good result in air quality data recording and presentation. It was able to give air quality level and early warning indicator through the map visualization. Finally, the system has potential to become new facilities which can be used to educate the pabulic about environmental conditions.Keywords: Air Quality, Low Cost Sensor, Microkontroler, Data Visualization, Urban Sensing